Is Implicit Theory of Mind a Real and Robust Phenomenon? Results From a Systematic Replication Study. - Kulke, Louisa; Von Duhn, Britta; Schneider, Dana; Rakoczy, Hannes (Psychological Science, 2018)
Recently, theory-of-mind research has been revolutionized by findings from novel implicit tasks suggesting that at least some aspects of false-belief reasoning develop earlier in ontogeny than previously assumed and operate automatically throughout adulthood. Although these findings are the empirical basis for far-reaching theories, systematic replications are still missing. This article reports a preregistered large-scale attempt to replicate four influential anticipatory-looking implicit theory-of-mind tasks using original stimuli and procedures. Results showed that only one of the four paradigms was reliably replicated. A second set of studies revealed, further, that this one paradigm was no longer replicated once confounds were removed, which calls its validity into question. There were also no correlations between paradigms, and thus, no evidence for their convergent validity. In conclusion, findings from anticipatory-looking false-belief paradigms seem less reliable and valid than previously assumed, thus limiting the conclusions that can be drawn from them.